Xenomonitoring as an epidemiological tool supporting post-stop surveillance of albendazole-ivermectin mass drug distribution in the Bougouni-Yanfolila evaluation unit, Sikasso, Mali, in 2023 - Lamine Soumaoro; Housseini Dolo; Yaya Ibrahim Coulibaly; Siaka Yamoussa Coulibaly; Salif Seriba Doumbia; Moussa Sangaré; Abdallah Amadou Diallo; Abdoul Fatah Diabaté; Michel Emmanuel Coulibaly; Ibrahima Dolo; Massitan Dembélé; Alpha Seydou Yaro; et al. (BMC Infectious Diseases)
Abstract Introduction Mali and Guinea share a border and are both endemic for lymphatic filariasis (LF). However, their progress towards eliminating this disease varies. Mali is currently in the LF transmission assessment survey phase (TAS), while Guinea continues to implement mass drug administration (MDA). As the populations of these two countries are closely related, and vectors are present, the emergence of LF is theoretically possible in the Bougouni-Yanfolila evaluation unit (EU). This XenoFil study, which combines xenomonitoring and serosurveillance in health facilities, was used as a surveillance tool to assess LF transmission. The aim is to detect the emergence of LF in cross-border areas within the Bougouni-Yanfolila EU, after the third LF transmission assessment survey (TAS3). Method In the Bougouni-Yanfolila EU, we conducted a cross-sectional study to collect mosquitoes in the villages and blood samples from 6 years old and above (≥ 6 years old). In June, August 2022, and January 2023, we conducted three entomological studies in two ecologically distinct villages. The Ifakara type C tent trap (IFAKARA), the gravid trap, and indoor Pyrethrum spray catches were used to collect mosquitoes. For qPCR, mosquito of the same species was sorted into pools of twenty for molecular analysis using qPCR. The infection rate / the parasite prevalence was generated by the PoolScreen® 2 software. Trained local health workers performed serological surveys using filariasis test strips. Results In. the two study villages, we collected a total of 4,732 mosquitoes, of which 989 belonged to the species Anopheles gambiae s.l. and 3,743 to species of the genus Culex sp. A total of 264 pools were formed, with the genus Culex spp. accounted for 79.92% (211/264), while the genus Anopheles represented 20.08% (53/264). In June 2022, only one pool (0.53%) of Culex spp. tested positive [95% CI: 0.01–2.89]. Positive Anopheles pools were absent. The blood of ten of the 2056 individuals had positive results [0.49% (10/2056)]. Among the positives, one belonged to 6–7 years, two to that of 8–17 years, and seven to that of 18 years and older. Of the positive volunteers, 0.6% (6/996) were from Yanfolila’s border health region. The average cost of XenoFil (entomology combined with serology) is 5,656,244 CFA francs (US$9070), and TAS has an average cost of 6,366,450 CFA francs (US$10209) in a survey conducted in one evaluation unit. Conclusions The new XenoFil approach proved to be an easy, effective, and relatively cheaper method for integrated LF surveillance in rural areas. From the perspective of integrated LF monitoring, XenoFil is needed for scaling up to other EU.